PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LEMARI ES DI PERUMAHAN MUSTIKA PRAKARSA KARAWANG - Riani Wulandari; Netti Nurlenawati; Dexi Triadinda (POLITEKNIK LP3I JAKARTA, 2024)
The goal of this study is to determine how price and brand perception affect consumers' decisions to buy products. Businesses in the electronics industry have the chance to satisfy consumer preferences because of the increased demand and necessity for refrigerator electronics. In an effort to grab consumers' interest and attention, they work to enhance their brand image. The sample strategy was purposeful sampling, which is a nonprobability sampling method. A sample of ninety-six respondents who resided in the Mustika Prakarsa Housing area and had two-door refrigerators was taken. Google forms are utilized to support techniques for gathering data. The techniques used to handle and evaluate data include tests of validity, partial t, simultaneous F, multicollinearity, heteroscedasticity, regression equation coefficient, and coefficient of determination. Version 29.0 of IBM SPSS was used to gather the data for the following data processing step. The results of the test indicate that price and brand perception both considerably and favorably affect consumers' decisions to buy, sometimes at the same time. Price and brand perception work together to influence decisions to buy by 30.7%. Keywords: Purchase Decision, Price, Brand Image.